Sales Management System Design And Promotion Media (Marketplace) Sales Of Umkm, Padang City (Perancangan Sistem Manajemen Penjualan Dan Media Promosi (Marketplace) Penjualan Umkm Kota Padang) - Aulia Hadi; Randy Permana (Universitas Putra Indonesia YPTK Padang, 2019)
Padang city as we know it is a tourist city which is a lot of tourist destinations of both domestic and foreign tourists. Therefore, more than 50% of the people of Padang city choose to trade as the basis of their lives. But now as technology develops, people are more dominant or want everything to be easy. Including for shopping. In a very large number of MSMEs that have not been touched by the community. Therefore, with technology, the sales system that was previously done traditionally can be input in an integrated system. Market Place is a form of modern market today. Does not need a place but can accommodate all SMEs in the city of Padang. With this Market Place, it is expected that the community can reach out to the Padang city MSMEs even further and the sales and promotion systems of these MSME products can be spread more widely and make the revenue generated from the sales of MSMEs be increased and maximum again and the management of the sales system can be well managed. With this marketplace application, it is expected that MSME entrepreneurs who do not have a permanent place can increase their income. There are at least 88.8 percent contributing to economic growth in Southeast Asia. In Indonesia, there are approximately 59.2 million MSME actors by contributing 56 percent of the country's add up to the economy. However, from the add up to UMKM, only 3.97 percent million MSMEs have entered online